Declaring Disaster : Buffalo's Blizzard of '77 and the Creation of FEMA - Kneeland, Timothy W., 1962- (Book collections on Project MUSE., 2021)
"Buffalo's 1977 blizzard was the first snowstorm to be declared a disaster in US history and, in "Declaring Disaster," Kneeland offers a compelling examination of whether the 1977 storm was an anomaly or the inevitable outcome of years of city planning. From the local to the state and federal levels, Kneeland discusses governmental response and disaster relief, showing how this regional event had national implications for environmental policy and how its effects have resounded through the complexities of disaster politics long after the snow fell"--